Autism - Glidden, Laraine Masters, 1943- (International review of research in mental retardation, 2000)
This special thematic volume on Autism in the International Review of Research in Mental Retardation series provides a comprehensive overview of research on autism today. Coverage includes discussion of the genetics, diagnosis, neural and cognitive basis, and development of autism, as well as an exploration of the effects of autism on language, attachment, and emotional responsiveness. A final chapter examines the psychological impact that raising an autistic child has on the family.